(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the international relations the special place is taken by ethnic information, and also ethnostereotypes which find reflection in this information. It is connected with that ideas and opinions of one nation on the character, labor skills, lifestyle, historical name of other people characterize interethnic relations of these ethnoses, and also influence dynamics of their development. The topicality of the research of ethnostereotypes is established in this aspect in the scientific article. Contributing to the establishment of the harmonious or, on the contrary, conflict interethnic relations, ethnostereotypes in the texts of mass media are expressed in different language means. In publications of mass media ethnostereotypes containing standardized representations, are expressed in a direct, indirect, and also in the hidden language form. In the scientific article language features of ethnic stereotypes on the materials of the national republican newspaper «Egemen Kazakhstan» and political independent newspaper «Kazakhiya» are considered.